2016
DOI: 10.18632/oncotarget.10007
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and methylation of genes related to lung cancer development

Abstract: Lung cancer is a leading cause of cancer-related mortality worldwide, and cigarette smoking is the major environmental hazard for its development. This study intended to examine whether smoking could alter methylation of genes at lung cancer risk loci identified by genome-wide association studies (GWASs). By systematic literature review, we selected 75 genomic candidate regions based on 120 single-nucleotide polymorphisms (SNPs). DNA methylation levels of 2854 corresponding cytosine-phosphate-guanine (CpG) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Indeed, we show here that shRNA-mediated downregulation of α5-nAChR in NSCLC cells inhibits tumor formation in vivo and causes increased apoptosis in A549 cells, high α5-nAChR protein expression is predictive of decreased lung cancer patient survival and is correlated with the clinical TMN stage, and, our in vitro and in vivo experiments support this idea that α5-nAChR is a tumor enhancer for nicotine-induced lung cancer. Several studies have shown that nAChRs regulate the growth and progression of lung ( Improgo et al, 2013 ; Gao et al, 2016 ) and other cancers ( Al-Wadei et al, 2012 ; Chu et al, 2013 ; Chernyavsky et al, 2015 ; Schaal et al, 2015 ; Zhao et al, 2015 ; Jia et al, 2016 ). Our findings here are in accordance with these results and further supported the idea that α5-nAChR mediates nicotine-induced lung cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we show here that shRNA-mediated downregulation of α5-nAChR in NSCLC cells inhibits tumor formation in vivo and causes increased apoptosis in A549 cells, high α5-nAChR protein expression is predictive of decreased lung cancer patient survival and is correlated with the clinical TMN stage, and, our in vitro and in vivo experiments support this idea that α5-nAChR is a tumor enhancer for nicotine-induced lung cancer. Several studies have shown that nAChRs regulate the growth and progression of lung ( Improgo et al, 2013 ; Gao et al, 2016 ) and other cancers ( Al-Wadei et al, 2012 ; Chu et al, 2013 ; Chernyavsky et al, 2015 ; Schaal et al, 2015 ; Zhao et al, 2015 ; Jia et al, 2016 ). Our findings here are in accordance with these results and further supported the idea that α5-nAChR mediates nicotine-induced lung cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on smoking history was also obtained from questionnaires, including age at initiation and smoking intensities at various ages, as well as the age of quitting smoking for former smokers. 54 Twenty-two and 17 participants with missing information on smoking status were excluded from the discovery and the validation panel, respectively. Additional information on body mass index (BMI) was extracted from a standardized form filled by the general practitioners during the health check-ups.…”
Section: Data Collectionmentioning
confidence: 99%
“…Rather, MR, which takes genetic variants randomized with respect to confounding factors as proxies for an exposure of interest (i.e., DNA methylation), may be used to identify causal effects, or reject spurious findings. The findings of this study do not preclude the possibility that other DNA methylation changes are causally related to lung cancer (or other smoking--associated cancers) (41). In addition, it is possible that DNA methylation at these CpG sites in lung tissue has a causal effect on lung cancer, which we were unable to directly evaluate here.…”
Section: Limitationsmentioning
confidence: 58%